Mental Health Inequalities During COVID-19 Outbreak: The Role of Financial Insecurity and Attentional Control. Issue 1 (12th November 2021) - Claes, Nele; Smeding, Annique; Carré, Arnaud
The COVID-19 pandemic and subsequent lockdowns negatively impacted the mental health of populations. This impact is not equally distributed and increases existing mental health inequalities. Indeed, government restrictions and the economic consequences of the pandemic affect more the less educated and less wealthy people. However, psychological processes implicated in this increase of mental health inequalities during the COVID-19 pandemic remain unexplored. The present study (N=591) tested the role of financial insecurity and attentional control in the relation between socioeconomic status and mental health, along with the influence of trait anxiety. Based on Structural Equation Modelling, findings showed a mediation effect of financial insecurity, but not of attentional control, in the relationship between socioeconomic status and mental health. In addition, exploratory analyses suggested that financial insecurity also mediated the effect of attentional control on mental health. Results of the present research point at the importance of understanding psychological processes implicated in the effect of economic crises on mental health inequalities.